The Study on the Social Science Methodology: Focusing on change in the behavior of Policymakers - Yeon Soo (Technium Social Sciences Journal, 2020)
This study aims to study on the research methodology. The methodology of social science can be divided into quantitative research and qualitative research. However, the dichotomous logic of research methodology is not enough to understand social phenomena and methodological researchers have not been able to broaden academic horizons so far. Therefore, this study aims to expand the horizon of the methodology and contribute to the academic and social consensus. The researchers sought to extend the methodology. This study was compared. The process of describing behavior change by applying phenomenology, hermeneutics, and criticism is the changes in behavior of policy decision makers.